Unmarried Cohabitation: A Question of Terminology - Vítečková, Miluše; Jílková, Lucie (Lidé města, 2011)
This article analyzes in-depth interviews with people who are not married, yet live together. This type of cohabitation, similar to marriage, but not conditioned by official legal marriage bonds, has been on the rise in the Czech Republic since the 1990s. The number of children born into this type of union is also increasing. The most common label for this type of union in specialized communication is nesezdané soužití [unmarried cohabitation]. The Czech Statistical Office is inclined toward the labels of de facto marriage or common-law marriage, and in the media and in everyday communication we can encounter phrases such as život na psí knížku or život na hromádce [shacking up, living in sin]. The in-depth interviews were conducted as a part of a qualitative research project realized in 2008-2010, and oriented toward what was originally a predominantly sociological analysis of unmarried cohabiting couples with children. A lexical and corpus analysis of the interviews revealed that the labels for this type of union, as well as the labels for the partners living in it, vary greatly. The respondents' attitudes toward the individual labels also vary. Only time will reveal whether any of the labels appearing in the interviews (přítel/přítelkyně, partner/partnerka, kamarád/kamarádka, druh/družka, milenec/milenka) [boyfriend/girlfriend, partner, friend, companion, lover] will become the dominant, definitive ones for unmarried partners.